2015
DOI: 10.1093/brain/awv370
|View full text |Cite
|
Sign up to set email alerts
|

Temporoparietal encoding of space and time during vestibular-guided orientation

Abstract: The cardinal features of vestibular dysfunction are illusory self-motion (vertigo) and spatial disorientation. Testing 18 acute focal cortical lesion patients, Kaski et al. show that temporoparietal junction lesions impair vestibular-guided spatial orientation but not self-motion perception. Distinct cortical substrates thus mediate the vestibular percepts of spatial orientation and self-motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 48 publications
6
58
0
Order By: Relevance
“…Although several brain regions are known to be involved in self-motion perception (Baier et al, 2013;Kaski et al, 2016;Nigmatullina et al, 2015), the insular and opercular cortices play an important role in multisensory integration of space-motion information for self-motion perception (Shinder & Newlands, 2014). These findings are consistent with reduced activity and connectivity of the PIVC, hippocampus and anterior insula observed in patients with CSD in a previous fMRI study (Indovina et al, 2015).…”
Section: Decreased Connectivity Of the Parieto-insularhippocampal-csupporting
confidence: 71%
See 1 more Smart Citation
“…Although several brain regions are known to be involved in self-motion perception (Baier et al, 2013;Kaski et al, 2016;Nigmatullina et al, 2015), the insular and opercular cortices play an important role in multisensory integration of space-motion information for self-motion perception (Shinder & Newlands, 2014). These findings are consistent with reduced activity and connectivity of the PIVC, hippocampus and anterior insula observed in patients with CSD in a previous fMRI study (Indovina et al, 2015).…”
Section: Decreased Connectivity Of the Parieto-insularhippocampal-csupporting
confidence: 71%
“…The human vestibular cortex is centered in the OP2 region of the opercular cortices (zu Eulenburg et al, ) and together with adjacent areas of the insula and temporal‐parietal junction constitutes the human homologue of the parieto‐insular vestibular cortex (PIVC) that has been identified in other species (Eickhoff, Weiss, Amunts, Fink, & Zilles, ). Although several brain regions are known to be involved in self‐motion perception (Baier et al, ; Kaski et al, ; Nigmatullina et al, ), the insular and opercular cortices play an important role in multisensory integration of space‐motion information for self‐motion perception (Shinder & Newlands, ). These findings are consistent with reduced activity and connectivity of the PIVC, hippocampus and anterior insula observed in patients with CSD in a previous fMRI study (Indovina et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have found normal path integration function with hippocampal lesions in humans but not rats (69). This conundrum has recently been solved by a recent human lesion study, which shows in fact that the important region is the temporoparietal junction (70). In addition, this study also found no impact of hippocampal lesions upon angular path integration function.…”
Section: The Vestibular Thalamic Projections and The Vestibular Cortimentioning
confidence: 99%
“…In addition, this study also found no impact of hippocampal lesions upon angular path integration function. It follows that dementia, which is more frequent in the elderly, may affect spatial orientation by its effect on vestibular cortical regions such as the TPJ (70). …”
Section: The Vestibular Thalamic Projections and The Vestibular Cortimentioning
confidence: 99%
“…In addition, this study also found no impact of hippocampal lesions upon angular path integration function. It follows that dementia, which is more frequent in the elderly, may affect spatial orientation by its effect on vestibular cortical regions such as the TPJ (70). Another currently unsolved question is the cortical location mediating the sensation of vertigo.…”
Section: The Vestibular Thalamic Projections and The Vestibular Cortimentioning
confidence: 99%